Strategi Komunikasi Persuasif dalam Pelayanan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Bapenda Kendal - Hilda Karnisya Rahmah; Agus Triyono (Jurnal Kajian dan Penelitian Umum, 2026)
Persuasive communication plays a crucial role in enhancing the effectiveness of public services, particularly in encouraging public compliance with tax obligations. This study aims to analyze persuasive communication strategies in Rural and Urban Land and Building Tax (PBB-P2) services at the Kendal Regency Regional Revenue Agency (Badan Pendapatan Daerah-BPN) and the factors influencing their effectiveness. This study employed a descriptive method with a qualitative approach, using in-depth interviews, observation, and documentation as data collection techniques. Data analysis was conducted using the Miles and Huberman interactive model, comprising data reduction, presentation, and conclusion drawing. The results indicate that persuasive communication strategies are implemented through clear service procedures, the use of communicative language, and the responsiveness of officers in addressing obstacles. These strategies are effective in fostering positive understanding and perceptions among taxpayers. However, service effectiveness still faces challenges in human resources and internal communication, which impact service consistency, primarily due to the imbalance between the number of officers and the workload. These findings suggest that the effectiveness of persuasive communication is determined not only by the quality of interactions between officers and taxpayers but also by the organization's internal preparedness to maintain consistent service quality.